Pelatihan Pelayanan Prima di KSPPS BMT KUBE COLOMADU SEJAHTERA - Putro, Tetuko Rawidyo; Sistriatmaja, Muhammad Bagus; Siti Aisyah Tri Rahayu; Hakim, Lukman; Hery Sulistyo Jati N S; Sumantyo, Riwi; Mulyanto; Johadi; Ariyanto Adhi Nugroho; Purnama, Muhammad Yusuf Indra (Yayasan Sagita Akademia Maju, 2024)
This service aims to improve the quality of human resources and the performance of KSPPS BMT KUBE COLOMADU SEJAHTERA employees by providing excellent service training to KSPPS BMT KUBE COLOMADU SEJAHTERA employees. The focus of the training is on efforts to improve employee performance so that they can provide an understanding of the importance of excellent service in internal and external interactions, Equip participants with an understanding of consumers as individuals who have many desires and perceptions about a product (service), Equip participants with the ability to provide excellent service, and be able to know the factors that influence consumer satisfaction and various methods of measuring excellent service. Enabling participants to be able to handle various complaints, access to financial institutions, both conventional and sharia, as well as financial technology. The approach used in this activity is to carry out training activities for employees to significantly improve the performance of BMT employees. It is hoped that the results of the training will be able to motivate and provide the skills needed for employees to provide excellent service to their customers. Excellent service to BMT customers will increase customer comfort and loyalty to BMT Kube Colomadu